Assessing ICT Competence among Secondary-Level Teachers in Kathmandu Valley - Simkhada, Anusha; Gelal, Arpan (Samriddhi Journal of Development Studies, 2023)
This study investigates the state of ICT integration in Kathmandu's school education system, particularly the ICT competency of secondary-level teachers. The research employed a quantitative methodology utilizing a close-ended questionnaire with 41 teachers from four community schools. The collected data was analyzed using t-tests and ANOVA through SPSS. Additionally, the qualitative insights from the interview complemented the research. The findings of the study reveal a moderate proficiency in ICT competency among secondary-level teachers, with the low competence observed in ICT knowledge and practice. This suggests that while teachers possess some basic ICT skills, they may not fully utilize ICT's potential in their teaching practices. Further, statistically significant relationship between age and ICT competency, with lower proficiency among older teachers, highlights a potential need for targeted training programs to address the skills gap. Regarding the qualitative aspects of ICT integration, a persistent reliance on traditional teaching methods despite the acknowledgment of ICT's potential was prevalent, particularly among the old teachers. This disconnect between awareness and implementation underscores the need for deeper pedagogical integration of ICT into the curriculum and teaching practices. Additionally, the research identifies gaps in policy and uneven training in ICT integration across schools, emphasizing the need for a more systematic and standardized approach to ICT adoption. Overall, the study provides valuable insights into the current state of ICT integration in the secondary education system in Kathmandu Valley and highlights the challenges and opportunities for enhancing ICT competency among secondary-level teachers. The findings offer practical recommendations for policymakers, school management, and individual teachers to promote effective ICT integration and elevate the quality of school education in Kathmandu